Association Between Blood Glucose Levels and Leukocyte Counts in Patients with Diabetic Gangrene: A Cross-Sectional Study - Nurseskasatmata, Satria Eureka; Sulistyawati, Wiwin; Christianingsih, Siska; Sulistyana, Caturia Sasti; Fauzi, Abdul; Jayani, Indah; Etika, Arif Nurma (Journal of Applied Nursing and Health, 2026)
Background: Diabetic gangrene is a severe complication of diabetes mellitus (DM) that often leads to amputation. DM increases susceptibility to infection by impairing leukocyte function. Although hyperglycemia is known to weaken innate immunity, its association with leukocyte count remains unclear, particularly in low- and middle-income country (LMIC) settings. This study aimed to assess the association between admission blood glucose levels and leukocyte counts in patients with diabetic gangrene. Methods: This study utilized a retrospective cross-sectional design and was prepared in accordance with the STROBE guidelines. Secondary data were extracted from the medical records and laboratory reports of patients hospitalized at Kertosono Regional General Hospital in East Java, Indonesia, from January to December 2022. A purposive total sampling approach was applied. Inclusion criteria required an inpatient diagnosis of diabetes mellitus with diabetic gangrene, alongside the availability of both random blood glucose and total leukocyte count results for the same admission. Exclusion criteria eliminated records with missing or illegible key laboratory values, duplicate records, and records lacking diagnostic confirmation in the discharge summary. The independent variable assessed was admission random blood glucose (mg/dL), and the dependent variable was the total leukocyte count (cells/µL). Results: From an initial pool of 50 records, a final sample of 38 medical records was selected for analysis. Spearman’s rank correlation indicated that there was no significant association between random blood glucose levels and total leukocyte counts (r = -0.031; p = 0.853). Conclusion: Admission blood glucose does not meaningfully track or correlate with total leukocyte count in patients presenting with diabetic gangrene. Clinically, this suggests that leukocyte count should not be used as a proxy or surrogate for acute glycemic status. Therefore, comprehensive infection severity assessments in these patients require integrating clinical evaluation with additional, more specific inflammatory indices.